Stability of grain yield of pre-commercial maize (Zea mays L.) hybrids in rainfed ecosystems of South Asia - Nagesh, Patne; Takalkar, Satish Ashok; Singh, Narendra Kumar; Sahoo, Smrutishree; Joshi, Anjali; Mohan, Sagala Murali; Pulime, Naga Bhaskara Naidu; Shrestha, Jiban; Vivek, Bindiganavile (Research Centre for Cereal and Industrial Crops, 2025)
A study was conducted to assess the yield stability of 45 single cross maize (Zea mays L.) hybrids across five locations in North India, namely Samastipur, Muzaffarpur, Meerut, Kannauj, and Varanasi. Of the 45 hybrids tested, 21 displayed a higher-than-average yield (3.76 t/ha) across all environments. The analysis of variance showed that environment contributed to 88.4% of the total variation, followed by genotype x environment (7.9%) and genotype (3.7%). The first two significant interaction principal component axes accounted for about 81.54% of the total variation for grain yield. Hybrid 39 had the highest yield under diverse environments. Meerut and Muzaffarpur were identified as being more representative for grain yield compared to Kannauj, Samastipur, and Varanasi. Meerut was found to be the most discriminating environment. Hybrid 27, with an AMMI (Additive main effects and multiplicative interaction) stability value (ASV) of 0.00, was widely adapted. Hybrids specifically adapted to Samastipur (2), Muzaffarpur (2), Meerut (1), Kannauj (2), and Varanasi (2) were identified. With the least yield stability index (YSI), Hybrid 40, is recommended for cultivation during the monsoon in Northern India. Meerut and Muzaffarpur sites are recommended for evaluating early stages of maize test crosses.